Evaluation of short- and long-term response to treatment in GIMEMA protocol for Acute Myeloid Leukaemia. (14th April 2010) - Ardoino, I.; Ambrogi, F.; Iacobelli, S.; Boracchi, P.; Manikis, G.; Kounelakis, M.G.; Zervakis, M.; Lisboa, P.J.G.; Fazi, P.; Vignetti, M.; Biganzoli, E.M.; Starita, A.
Acute Myeloid Leukaemia (AML) is a haematologic malignancy. Despite of improvements in prognosis it is still a severe disease and only a minority of patients are cured. Recently, insights into specific cytogenetics and biological aberration involved in the leukaemogenesis process are the target of research. LAM-99P GIMEMA Protocol identifies treatment guidelines for AML in adults. A methodological approach is proposed, compounding different modelling techniques, to assess the prognostic relevance of clinical as well as biological markers with regard to clinical endpoint, such as the achievement of Complete Remission in the short-term and long-term survival taking into account competing risks.